VARIATION OF MORPHOLOGICAL AND POMOLOGICAL CHARACTERS OF SOME POMEGRANATE GENOTYPES IN NORTH-WESTERN REGIONS OF SYRIA - Gassan Abdullah (Mesopotamia Journal of Agriculture)
Nine Pomegranate genotype 15-years old grown at Darkoush area in north-western regions of Syria were studied and harvested during the season of 2009 . physical and chemical composition of these genotypes fruits have been examined. The results Obtained are presented in the statistical tables. Based on those results the following results has been monitored : Trees variation between large in SD2,SD8 and small in SD1. fruits were in different colors ranging from pink and bleached greenish yellow to dark purple color, and fruitlets( the main edible part) had floral to red color. Leaf area in new growth from 4.24 cm2 in SD5 to 9.67 cm2 in SD6, but in old wood branches 4.37 cm2 in SD4 to 9.05 cm2 in SD1.The SD7 type Download the highest proportion of flower in old wood branches in comparison with other types.The highest proportion of bell flowers are you in SD6 and the least ratio in SD7. And contrary to the form of a pitcher who gives fruits .The average of the fruit ranges from 518.67 g. in SD7 TO 220 g. in SD9. The values of T.S.S. are 14.94 % in SD9 to 19.41 in SD5. The sweetness index(Flavor index) i.e. T.S.S/TA amounts to 34.89 in SD4 whale it is 4.89 in SD9.